The nearly complete mitochondrial genome of the door snail Euphaedusa aculus (Stylommatophora: Clausiliidae) and phylogenetic analysis - Qi-Chao Liang; Ke-Xin Tao; Dong-Dong Qiao; Pei Wang; Hao-Fei Yin; Qian-Qian Yang (Mitochondrial DNA. Part B. Resources)
The family Clausiliidae was proposed as a model for studying the diversity of breeding biology in land snails. This study assembled a nearly complete mitogenome (15,417 bp) for the clausiliid snail Euphaedusa aculus. The mitogenome includes 13 protein-coding genes (PCGs), two ribosomal RNAs, and 22 transfer RNAs, with a gene order consistent with other clausiliids. Most PCGs use ATN start codons and complete stop codons, except for atp6, nad4, and nad5, which start with TTG, and atp6, cox3, and nad3, which have incomplete stop codons. Phylogenetic analyses revealed that E. aculus is closely related to E. planostriata. This mitogenome provides a valuable molecular resource for future evolutionary research on land snails.